The Potential of Pomegranate as a Therapy for Thyroid Eye Disease: A Systematic Review - Wahyuni, Devi Azri; Parisa, Nita; Tribowo, Anang; Harahap, Debby Handayati (Biomedical Sciences and Clinical Medicine, 2026)
Pomegranate (Punica granatum), a natural antioxidant, may help reduce oxidative stress and inflammatory markers in thyroid eye disease (TED), an autoimmune disorder affecting approximately one-third of patients with thyroid disease. This systematic review evaluated its efficacy and safety in TED management. Following PRISMA 2020 guidelines, a comprehensive search of ScienceDirect, PubMed, and SagePub identified English-language full-text articles published from 2010 to 2024. Editorials and non-DOI reviews were excluded. From over 400 publications screened, eight met the inclusion criteria. Evidence suggests that quercetin, a key flavonoid in pomegranate, can neutralize superoxide anions, inhibit lipid peroxidation, and induce apoptosis in tumor cells. In-vitro studies further indicate that quercetin suppresses fibroblast proliferation and reduces hyaluronic acid secretion in TED. These findings support pomegranate’s potential as an adjunct therapy for TED; however, further clinical trials are needed to establish optimal dosage, formulation, and bioavailability for therapeutic use.